Design and Analysis of New Harbour Grid Models to Facilitate Multiple Scenarios of Battery Charging and Onshore Supply for Modern Vessels - Kumar, Jagdesh; Memon, Aushiq Ali; Kumpulainen, Lauri; Kauhaniemi, Kimmo; Palizban, Omid (MDPI, 2019)
The main objective of this study is to develop and analyse diﬀerent harbour grid conﬁgurations that can facilitate the charging of batteries for modern vessels and supply onshore power. The use of battery energy storage systems in modern hybrid or entirely electric vessels is rapidly increasing globally in order to reduce emissions, save fuel and increase energy eﬃciency of ships. To fully utilise their beneﬁts, certain technical issues need to be addressed. One of the most important aspects is to explore alternative ways of charging batteries with high power capacities for modern vessels. The paper presents a comprehensive overview of battery-charging conﬁgurations and discusses the technical challenges of each design from the perspective of their practical implementation, both onshore and onboard a vessel. It is found that the proposed models are suitable for vessels operating either entirely on battery storage or having it integrated into the onboard power system. Moreover, the proposed charging models in a harbour area can solve the problem of charging batteries for future hybrid and electric vessels and can open new business opportunities for ship owners and port administrators. The performance of the proposed models is validated by simulating two case studies in PSCAD: slow charging (based onshore) and fast charging (based onboard).
Keywords: Battery charging; Battery energy storage system; Emissions; Harbour grid; Onshore power supply; Ship; fi=Sähkötekniikka|en=Electrical Engineering|